2020
DOI: 10.1109/jtehm.2020.3005308
|View full text |Cite
|
Sign up to set email alerts
|

Total Iron Measurement in Human Serum With a Novel Smartphone-Based Assay

Abstract: Background: Abnormally low or high blood iron levels are common health conditions worldwide and can seriously affect an individual's overall well-being. A low-cost point-of-care technology that measures blood iron markers with a goal of both preventing and treating iron-related disorders represents a significant advancement in medical care delivery systems. Methods A novel assay equipped with an accurate, storable, and robust dry sensor strip, as well as a smartphone mount and (iPhone) app is used to measure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(119 citation statements)
references
References 35 publications
5
111
0
3
Order By: Relevance
“…The aggregation and the instability are the main drawbacks of using SPIONs at physiological pH. To overcome these limitations, various surface coatings have been used to modify their surface properties [ 22 ]. It was also demonstrated that modification of SPIONs with carboxyl (-COOH) groups provide appropriate sites can be conjugated with any drugs and/or natural compounds containing amine (-NH 2 ) group or their combinations [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aggregation and the instability are the main drawbacks of using SPIONs at physiological pH. To overcome these limitations, various surface coatings have been used to modify their surface properties [ 22 ]. It was also demonstrated that modification of SPIONs with carboxyl (-COOH) groups provide appropriate sites can be conjugated with any drugs and/or natural compounds containing amine (-NH 2 ) group or their combinations [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data is obtained from our laboratory-custom apparatus in a comma-separated values (csv) file with the corresponding red, green and blue (RGB) intensities for the reference and sensor strip, and absorbance for each component is also provided [17, 18]. The calibration curve was plotted as the difference between the average of the red absorbance for the three strips at the end of the experiment and the corresponding to 0 ppm (MilliQ water).…”
Section: Methodsmentioning
confidence: 99%
“…Depending on the physicochemical nature and the chemical profile of the plant molecules to be encapsulated, several kinds of formulations have been used to increase their bioavailability, with lipid-based systems and especially liposomes being the most common ones. On the other hand, non-liposomal approaches include polymeric nanoparticles [ 14 ], nanoemulsions [ 15 , 16 , 17 ], quantum dots [ 18 ], micelles [ 19 ] and solid lipid nanoparticles.…”
Section: Challenges In the Use Of Plant Bioactive Ingredientsmentioning
confidence: 99%